CHERRY CV BIGARREAU NOIR GROSSA (MISRI) PRODUCTION AS INFLUENCED BY DIFFERENT INTERCROPS AS INFLUENCED BY DIFFERENT INTERCROPS - RIFAT BHAT; SHARBAT HUSSAIN, W. M. WANI,; M. K. SHARMA, NAWSHEEN NAZIR, MUZAFFARA AKHTER,; SANDEEP KUMAR, YOUSRA ALI BASU, AROOSA KHALIL, (The Bioscan, 2018)
Effect of intercrops viz., maize, pea, strawberry, cabbage, red clover, french bean, oats and clean cultivation (control) on Cherry cv Bigarreau noir grossa (Misri) production as influenced by different intercrops, was studied during the years 2008 and 2009 under Kashmir conditions. Cherry trees bearing the age of 9 years were grafted on Colt rootstock and were spaced at the distance of 4x4 m2 . Plot size was 16 m2. The results obtained revealed significant improvement in cherry trees intercropped with leguminous crops like pea, red clover and french bean than clean cultivation and heavy feeder crops (requiring high level of soil nutrients) like strawberry, cabbage, oats and maize. Highest per cent fruit set( 13 %), fruit maturity (75 DAFB up to date of harvesting), fruit yield (17.75 kg/tree) fruit weight (4.08g), fruit Anthocyanin (4.47 mg/g of fruit) and fruit physico-chemical characteristics like fruit TSS (19.98%), Fruit Acidity (0.72%) and Total Sugars (11.20%) were recorded maximum in cherry trees with leguminous type of crops i.e pea and red clover respectively.